Nötkött : kriterier vid inköp av nötkött i restaurangbranschen - Edvinsson, Daniel (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
Swedish beef production has during the past year decreased while the consumption has increased. It´s imported beef that takes market shares. The purpose with this degreeproject is to investigate if the restaurants in Sweden are using imported or Swedish beef and the reason for their choice. The purpose is to find out if there is something the Swedish beef producers can change to increase Swedish beef in restaurants. My expectation is that the demand for Swedish beef will increase in restaurant and later even among consumers. I have interviewed ten chiefs in different restaurants and asked them the following questions: Is it the price, quality or something else that influences your choise? Does it matter to their customers if they serve Swedish or imported beef? How is the marketing of Swedish beef? It appeared both Swedish and imported beef on the restaurants. The general opinion was that Swedish beef was bad marbled and tasteless. But there was Swedish beef that is good but the supply of it is poor. It was the quality of the beef and not the price that affect their choice. The marketing of Swedish beef was usually done by wholesalers, not by the producers. The beef that the restaurants bought came from light breedes that was grown on pastureland and pasture. That´s why the cows of light breeds and mixes with them must increase in Sweden, as the meat from these animals has the quality that the restaurants demand. The supply of Swedish beef must improve so the restaurants can acces it the whole year.